The Dental and Oral Significance of Hutchinson-Gilford Prfogeria Syndrome - Saeed, Safa; Abdulaziz Alhababi , Jawaher; Alanazi, Fatimah; Albarrak, Amal; Alabdulmonem, Halh; Inad Alenazi, Alanoud; Alsane, Maha; Akshay Kiran , Myle (Galen Medical Journal, 2025)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a rare genetic disorder caused by a point mutation in the LMNA gene that encodes lamin A. This mutation results in the production of progerin, a defective protein that accelerates cellular aging. This review explores the oral and dental manifestations of HGPS, emphasizing their role in early diagnosis, management strategies, and the potential for targeted therapies. A thorough review of existing literature was conducted to summarize the phenotypic characteristics, oral health implications, and current approaches for the management of HGPS-related complications. Individuals with HGPS exhibit age-associated complications starting in early childhood, including distinct craniofacial abnormalities and severe oral health challenges. Common oral manifestations include delayed tooth eruption, microdontia, malocclusion, dental caries, tooth loss, and mandibular osteolysis. These abnormalities necessitate a multidisciplinary approach involving pediatric dentists, orthodontists, oral surgeons, and geneticists to deliver comprehensive care. Understanding the pathophysiological mechanisms behind HGPS oral anomalies is vital for improving diagnosis and treatment. Advances in genetic research hold promise for developing targeted interventions to alleviate dental complications and enhance the quality of life for affected individuals. Ongoing research and a collaborative care approach are essential to address the challenges posed by HGPS effectively.